Pengaruh On The Job Training Terhadap Kinerja Karyawan (Studi di PT Kereta Api Indonesia (Persero) Kantor Pusat Bandung) - Permatasari, Intan Widia; Chaniago, Harmon (Jurnal Riset Bisnis dan Investasi, 2018)
Nowadays, a company should be able to survive and compete against a changes in the business, therefore companies must be competitive in order to survive from changes that happen. One of actions that company takes to survive and compete is to improve the ability of major assets of the company itself, human resources. Job training in a company is the company's actions to improve the ability of employees to be able perform the duties and obligations as an employee, so the company's objectives will be achieved. One of job training often done by company is on-the-job training. Training the work which is done by the company will have an impact on both the poor level of the employee's performance. This research aims to determine the relationship between on-the-job training and employee performance. In this research , the object is PT Kereta Api Indonesia (Persero) Bandung Head Office which is a state-owned company engaged in the field of land transportation services. To know the relationship of both, the research method that is used is quantitative with interview techniques, questionnaires, literature, and calculations using SPSS for testing the hypothesis that using Pearson Product Moment correlation analysis, simple regression analysis, and test R square.